Pelatihan Pemanfaatan Konten MOOC Untuk Meningkatkan Keterampilan Riset Inovasi Konselor di Sekolah - Zamroni Zamroni; Diniy Hidayatur Rahman; Ella Faridati Zen (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2026)
The aim of this study is to determine the effectiveness of training in the use of Massive Open Online Course (MOOC) content in enhancing participants’ knowledge and skills, particularly in the context of developing innovative guidance and counselling services in schools. The training participants consisted of 15 counsellors affiliated with the MGBK SMP in Malang Regency. The research method employed was a quantitative approach using a pre-test–post-test design to measure the participants’ increased knowledge regarding the definition, characteristics and advantages of MOOCs following the training. The results of the statistical analysis indicate that there was no significant improvement (Z = -1.723, p = 0.085 > 0.05) in cognitive performance following the training. Nevertheless, in practical terms, participants demonstrated a good ability to use the MOOC platform, access and utilise the training content, and complete the tasks assigned via the system.